Perceived Value and Adoption Intention for 5G Services in India: Moderating Effect of Environmental Awareness - Kala, Devkant; Chaubey, Dhani Shanker (Journal of Telecommunications and the Digital Economy, 2024)
Acknowledgment of the significance of environmental factors in technology adoption is widespread. However, empirical investigations into how environmental awareness influences the interconnection between perceived value and adoption intention for 5G services are notably lacking. This study investigates how perceived value shapes consumers’ 5G adoption intentions and how environmental awareness moderates the relationship between perceived value and adoption intention, employing the Value Adoption Model (VAM). Survey items on perceived value, adoption intention, and environmental awareness, drawn from existing literature on consumer value and information systems, were employed to gather data. An online questionnaire was completed by 530 participants from India. The collected data was processed using PLS-SEM. The findings indicate that perceived usefulness and enjoyment are key drivers of adoption, while perceived costs show mixed effects. Notably, technical issues do not negatively impact perceived values, but perceived fees negatively affect the perceived value of 5G services. Overall, perceived value significantly influences 5G adoption intention, with environmental awareness mediating this relationship. The findings offer valuable guidance to 5G service providers in emerging markets and provide policymakers with insights into the interplay of cost-benefits and environmental considerations in 5G service adoption.